Cognitive Behavioral Therapy for Children With Headaches: Will an App Do the Trick?. (March 2023) - Moyes, Carinna; Belaghi, Reza; Webster, Richard J.; Whitley, Nicole; Pohl, Daniela
Participants were enrolled into a pilot randomized-controlled 4-week trial comparing the efficacy and feasibility of app-based cognitive behavioral therapy (CBT) to a stretching program. Headache-related disability and quality of life were assessed using the Pediatric Migraine Disability Scale (PedMIDAS), Kidscree27, and Pediatric Quality of Life Inventory. Multivariable regression analysis were performed to assess the group effects in the presence of adherence and other covariates. Twenty participants completed the study. Adherence was significantly higher in the stretching than in the CBT app group (100% vs 54%, P  < .034). When controlling for adherence and baseline scores, the stretching group showed greater reduction in PedMIDAS score (average: 29.2, P  < .05) as compared to the CBT app group. However, in terms of the Quality-of-Life Indicators, pre- and postintervention raw scores were not significantly different between groups ( P  > .05). App-based CBT was not superior to a stretching program in reducing headache-related disability in a select population of pediatric headache patients. Future studies should assess if implementing features to the CBT app, like tailoring to pediatric age groups, would improve outcomes.